Effect of transverse dissipative particle dynamics on dynamic properties of nanometer-thick liquid films on solid surfaces. Issue 16 (1st November 2020) - Kobayashi, Takayuki; Zhang, Hedong; Fukuzawa, Kenji; Itoh, Shintaro
ABSTRACT: To ascertain the effect of transverse dissipative particle dynamics (DPD), which includes lateral dissipative forces in addition to the central ones in the standard DPD, on dynamics of systems involving interfaces, we compare dynamic properties derived from coarse-grained (CG) molecular dynamics simulations with the standard and transverse DPD for nanometer-thick liquid films on solid surfaces. The dynamic properties include relaxation times of the film thickness distribution and molecular rotational motion, and transport properties associated with molecular translational motion. Our results show that these dynamic properties are tuneable by changing friction coefficients in the transverse DPD, whereas this is not the case in the standard DPD. We also confirm that the transverse DPD applied to liquid–solid CG bead pairs can tune dynamic properties of nanometer-thick liquid films on solid surfaces, though it is less effective than when applied to liquid–liquid CG bead pairs. Moreover, we reveal that the dissipative forces are isotropic in transverse DPD, whereas the liquid–solid dissipative forces are highly anisotropic and nearly along the direction perpendicular to solid surfaces in standard DPD. This suggests that the transverse liquid–solid DPD might be crucial for modelling the in-plane energy dissipation at liquid–solid interfaces.